Natural Products and Nanotechnology Against Coronavirus Disease 2019 - Zeng, Ning; Chen, Xue; Liu, Zeming (Frontiers in Chemistry, 2022)
Coronavirus disease 2019 (COVID-19) is a new and severe infectious disease and new global disaster and is spreading rapidly worldwide. Natural products have a long history and have been widely used to treat various acute, chronic, and even life-threatening diseases worldwide. However, the natural products have reduced bioavailability and availability as they have poor kinetic properties, such as large molecular weight, inability to cross lipid membranes, and weak absorption ability. With the rapid development of nanotechnology, using novel nanotechnology in conjunction with natural products can effectively eliminate the molecular restriction of the entry of nanoproducts into the body and can be used to diagnose and treat various diseases, including COVID-19, bringing new strategies and directions for medicine. This article reviews the role and implementation of natural products against COVID-19 based on nanotechnology.